PROCESSING OF SORGHUM FROM DIFFERENT VARIETIES AND HYBRIDS FOR SEMOLINA AND THEIR PRODUCTS - U.D. Chavan; S.S. Patil; B. Dayakar Rao; J.V. Patil (Indonesian Journal of Agricultural Science, 2015)
The present study was undertaken with the objective to standardise procedures for preparation of semolina (rava) from sorghum, to identify the best genotype for preparation of semolina and to study the nutritional quality parameters of semolina. For processing of sorghum, ten varieties and five hybrids were used for preparation of semolina and their products. A process has been standardized for semolina preparation using ultra grinding mill from sorghum grain. The semolina yield ranged from 46.51% to 54.29%. Hybrid CSH-15R gave the highest yield of semolina (54.29%). Starch content in semolina ranged from 59.93% to 66.43%. The new genotypes Phule Vasudha, Phule Yashoda and M 35-1 showed higher levels of starch content as compared to the other genotypes. The Phule Vasudha and Selection-3 showed higher levels of total soluble sugars in grains, as well as in semolina than the other genotypes. Phule Maulee gave higher level of crude fibre content (3.12%). The amino acid profile of sorghum grain and semolina showed very minor differences in the content due to the processing of sorghum grains into various products like semolina. The new genotypes of rabi sorghum showed comparable results for the mineral with that of hybrids. The organoleptic properties of the sweet (shira), upama and idali prepared from semolina were judged on the basis of colour, texture and appearance, flavour, taste and overall acceptability of the products using semi-trained judges and 1 to 9 hedonic scales. All products prepared from semolina were like very much and gave highest rating of more than 8 hedonic scales. While considering the yield of semolina from sorghum grains as well as their nutritional composition and organoleptic properties of the niche products (shira, upama, idali) prepared from them, the varieties Phule Vasudha and Phule Yashoda were the best one as compared to the other varieties and hybrids and overall varieties were better than the hybrids.